An online framework for introducing STI point-of-care tests in Pacific island countries and areas - Lisa Natoli; Benjamin Coghlan (World Health Organization Regional Office for the Western Pacific, 2012)
Sexually transmitted infections (STIs) are an important public health issue in Pacific island countries and areas. Diagnosis is challenging, often requiring laboratory facilities and technical expertise rarely available. Patients seldom have results before they leave the health facility, with management primarily based on symptoms. As the delay between testing and treatment increases, so does the potential for complications of infection for the individual, the likelihood of STI transmission to other sexual partners and the chance the client will not return for follow-up. Effective tests that can be used at the point of care (POC) can conceivably overcome these consequences of delayed diagnosis. Such tests for STIs are becoming more available and affordable, with the potential to improve STI control. However, the introduction of POC tests is complex, requiring consideration of a range of implications to operationalize testing successfully and minimize potential harms.